Effect of deficit irrigation on Helianthus annuus L. plants in containers - Orejuela-Romero, Jennifer; Chipantiza-Masabanda, Juan; Carrera-Oscullo, Pablo; Salguero-Cajo, Ana (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
In order to evaluate changes related to plant physiology, infrared thermography has been chosen as a non-invasive complement. The research objective was to analyze the effect of deficit irrigation on Helianthus annuus L. plants in containers by means of IR thermography in a controlled experimental population at the University of Seville. The experiment consisted of three irrigation treatments to sunflower plants; one treatment received full irrigation (C-100) and two treatments received deficit irrigation: 70 % (R-70) and 50 % (R-50). A randomized block design was used. In the initial stage, polystyrene seedling trays of 54 cells (square) were used for the cultivation of sunflowers. The dimension of the trays was 700 x 400 x 70 mm.  The cell size was 65 x 70 mm and the capacity was 135 cm3.   For the development stage, plastic pots with a capacity of 4 L and a dimension of 21 x 16.4 cm were used. The sunflower plants used in this study did not exhibit significant differences in temperature and physiological analyses as a function of the irrigation treatment applied. However, there was a strong tendency for the plants to better resist water stress under a restrictive irrigation of 70%.